2019
DOI: 10.1101/834499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High density cultivation for efficient sesquiterpenoid biosynthesis inSynechocystissp. PCC 6803

Abstract: Cyanobacteria and microalgae are attractive phototrophic host systems for climate-friendly production of fuels and other high-value chemicals. The biosynthesis of an increasing diversity of industrially relevant compounds such as terpenoids has been demonstrated in recent years. To develop economically feasible and sustainable process designs, major challenges still remain regarding intracellular carbon partitioning, specific metabolic pathway activities and efficient cultivation strategies. Here, we present a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Curiously, under these conditions of high inorganic carbon availability, we observed little, but significant, difference in growth rate in the sucrose-exporting strains despite a significant rate of carbon export in the form of sucrose (Figures 2A, B, E). Since nutrients in BG-11 medium can become limiting at higher density, we next evaluated an enriched medium (CD) designed to support high-density cultures, such as those achievable in the HDC system (Dienst et al, 2020). When cultures were grown in CD media, non-exporting strains reached 11.1 OD 750 over the course of 5 days (Figure 2C), while also secreting a disproportionally high level of sucrose for an uninduced culture (Figure 2D).…”
Section: Optimizing High Cell Density Cultivation With Increased Irra...mentioning
confidence: 99%
“…Curiously, under these conditions of high inorganic carbon availability, we observed little, but significant, difference in growth rate in the sucrose-exporting strains despite a significant rate of carbon export in the form of sucrose (Figures 2A, B, E). Since nutrients in BG-11 medium can become limiting at higher density, we next evaluated an enriched medium (CD) designed to support high-density cultures, such as those achievable in the HDC system (Dienst et al, 2020). When cultures were grown in CD media, non-exporting strains reached 11.1 OD 750 over the course of 5 days (Figure 2C), while also secreting a disproportionally high level of sucrose for an uninduced culture (Figure 2D).…”
Section: Optimizing High Cell Density Cultivation With Increased Irra...mentioning
confidence: 99%
“…48 A recent study reported a yield of 17.3 mg L -1 patchoulol from Synechocystis using a High-Density Cultivation (HDC) system. 40 Though an impressive yield, it is based on smallscale (8 mL) cultures grown to an OD750 of 32 under 750 µE m -2 s -1 light, and the authors noted that specific productivity did not increase compared to batch cultures. For small-scale cultures that did not receive increasing light or media replenishment during growth and were supplied 100 µE m -2 s -1 light (growth conditions comparable to this work), yields of patchoulol were reduced to 590 µg L -1 , around two-fold greater than the highest yield achieved in this work.…”
Section: Heterologous Terpenoid Production From Thismentioning
confidence: 99%
“…In Synechocystis, expression of the patchoulol synthase gene under a strong copper inducible promoter yielded 17.3 mg L -1 patchoulol. 40 That study utilized a highly optimized small-scale High-Density Cultivation (HDC) system with nutrient rich media, bicarbonate, and increasing light intensity. The impressive patchoulol yield achieved reflects the high cell densities that can be reached using HDC; however, when grown under typical batch conditions, the yields were similar to those achieved for other terpenoids.…”
mentioning
confidence: 99%